PENINGKATAN MINAT DAN PRESTASI BELAJAR IPS MELALUI LEMBAR KEGIATAN SISWA BERBASIS LIFE SKILL - Marvilina Pusparia AS dan Samsi Haryanto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
The purpose of research is to determine the increase in interest and social studies achievement of students through Student Activity Sheet (LKS) based LifeSkill fourth grade students Potorono Banguntapan District of Bantul, Yogyakarta. This classroom action research was done 2 cycles with four stages: planning,implementation, observation, and reflection. Data collection technique used observation, interview, test learning outcomes, and questionnaires. The resultsshowed that the percentage of student interest increased from 20.83% to 91.67%,student achievement increased from 50% to students who achieve KKM 70 reached91.67% of the total number of students.